Adaptive Evolution of Community Response Organizations in Public Health Emergencies: A Grounded System Dynamics Case Study from China - Xianjun Guan; Changwei Qin; Tangzhenhao Li; Mengmeng Shan (Systems, 2026)
Public health emergencies often unfold over extended periods and place sustained pressure on community-level governance, particularly when demands for supplies, information, medical access, and daily support exceed routine service capacity. This study examines how community response organizations develop adaptive capacity under such conditions, drawing on a Shanghai community during the 2022 COVID-19 lockdown. Grounded theory was used to analyze semi-structured interviews, field observations, archival documents, and online community records and to identify the process through which fragmented resident mutual aid developed into organized collaboration. The grounded analysis identifies four linked stages of organizational evolution: capacity building, structural emergence, institutional consolidation, and experience accumulation. Building on these findings, a system dynamics model formalizes selected causal relationships and explores the feedback interactions among demand pressure, material reserves, information gaps, panic, volunteer mobilization, organizational division of labor, institutional support, and trust. The analysis illustrates how, within the proposed mechanism, resident participation may be activated through social capital, stabilized through institutional coordination and rule support, and sustained through feedback linking service performance, information reliability, trust, and continued participation. The study provides a feedback-based explanation of how community response capacity develops under prolonged emergency pressure and clarifies how informal resident action and formal governance arrangements can become mutually reinforcing. These findings contribute to research on community emergency adaptation and offer implications for grassroots preparedness, volunteer coordination, and collaborative governance.